CdTe quantum dots induce activation of human platelets: implications for nanoparticle hemocompatibility - Samuel SP (Dove Medical Press, 2015)
Stephen P Samuel,1 Maria J Santos-Martinez,2–4 Carlos Medina,2,3 Namrata Jain,1 Marek W Radomski,2,3 Adriele Prina-Mello,1,5 Yuri Volkov1,5 1Department of Clinical Medicine, Institute of Molecular Medicine, Trinity College Dublin, Dublin, Ireland; 2School of Pharmacy and Pharmaceutical Sciences, Trinity College Dublin, Dublin, Ireland; 3Trinity Biomedical Sciences Institute, Trinity College Dublin, Dublin, Ireland; 4School of Medicine, Trinity College Dublin, Dublin, Ireland; 5AMBER and CRANN, Trinity College Dublin, Dublin, Ireland Abstract: New nanomaterials intended for systemic administration have raised concerns regarding their biocompatibility and hemocompatibility. Quantum dots (QD) nanoparticles have been used for diagnostics, and recent work suggests their use for in vivo molecular and cellular imaging. However, the hemocompatibility of QDs and their constituent components has not been fully elucidated. In the present study, comprehensive investigation of QD–platelet interactions is presented. These interactions were shown using transmission electron microscopy. The effects of QDs on platelet function were investigated using light aggregometry, quartz crystal microbalance with dissipation, flow cytometry, and gelatin zymography. Platelet morphology was also analyzed by phase-contrast, immunofluorescence, atomic-force and transmission electron microscopy. We show that the QDs bind to platelet plasma membrane with the resultant upregulation of glycoprotein IIb/IIIa and P-selectin receptors, and release of matrix metalloproteinase-2. These findings unravel for the first time the mechanism of functional response of platelets to ultrasmall QDs in vitro. Keywords: platelets, quantum dots, aggregometry, flow cytometry, zymography, quartz crystal microbalance, transmission electron microscopy